The Effect of Shade from Two-Year-Old Oil Palms (Elaeis guineensis Jacq) on the Quality of Chili Pepper Seeds (Capsicum frutescens L.) - Darmawansyah; Muhamad Achmad Chozin; Edi Santosa; Arya Widura (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Chili pepper (Capsicum frutescens L.) is a seasonal crop with high economic value and is widely cultivated in both highland and lowland areas of Indonesia. As an important horticultural commodity and a staple ingredient in Indonesian cuisine, improving chili productivity requires rapid, accurate methods for seed quality assessment. The physiological quality of chili pepper seeds plays a crucial role in germination success and seedling establishment. Therefore, information regarding seed quality variation among genotypes is essential for selecting superior seed sources. This study aimed to evaluate the seed quality of five Capsicum frutescens genotypes based on viability, vigor, and membrane integrity parameters. The experiment was arranged in a randomized complete block design with four replications, using genotype as the treatment factor. Observations included germination percentage (GP), maximum growth potential (MGP), radicle emergence (RE), vigor index (VI), growth rate (GR), growth synchrony (GS), normal seedling dry weight (NSDW), seedling growth rate (SGR), electrical conductivity (EC), and tetrazolium viability (TZ). Analysis of variance revealed that genotype had a highly significant effect on all observed parameters at the 1% level of significance (α = 0.01). Genotype G3 exhibited the highest performance in key viability and vigor parameters, with GP of 71.50%, MGP of 77.50%, RE of 54.50%, VI of 55.00%, GR of 54.70% etmal⁻¹, GS of 60.50%, NSDW of 0.284 g, SGR of 0.00795 g KN⁻¹, and TZ viability of 88%, accompanied by the lowest EC value (17.792 µS cm⁻¹). In contrast, genotypes G1 and G4 showed the lowest values across most parameters, whereas G2 demonstrated moderate performance with relatively high vigor. These findings indicate that the physiological quality of cayenne pepper seeds varies among genotypes and is strongly influenced by genetic factors. This study provides valuable insights into seed quality under shaded conditions and contributes to the development of strategies for improving chili growth and adaptability in shaded environments.